Modern urban designing in the Philippines, 1898-1916 - Morley, Ian (Philippine Studies: Historical and Ethnographic Viewpoints, 2016)
The importation of modern American urban design practices into East Asia during the opening decades of the twentieth century fundamentally redefined the environmental form of cities. Although it is acknowledged that the introduction of the City Beautiful led to the endorsement of spatial forms dissimilar to what had hitherto existed, not much is currently known about (a) why city planning became such a fundamental component of governance at that time and (b) what impact urban design had upon the local civilization and the construction of nationhood. Consequently this article investigates the form and meaning of the first generation of Asian City Beautiful projects implemented prior to 1916 as part of America’s early colonial administration of the Philippines.